TINJAUAN GEOGRAFIS OBJEK WISATA GOA PUTRI - Elyus Juniwan; Zulkarnain Zulkarnain; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
This research aimed to describe the geographical condition of  Goa Putri’s tour object in the village of Padang Bindu District Semidang Aji Komering Ulu Ogan South Sumatera province, a pressure point study of landscape, location, climate, accessibility and facilities.                                          This study uses descriptive method. Object of this research is goa putri’ tourism area, the subject of research are managers, tourists and the public. Data collection by observation, structured interviews, and documentation. Data analysis is descriptive analysis techniques to determine the landscape, location and climate and scoring techniques to determine the formula for the model Struges accessibility and facilities. The results showed that, (1) Attraction Goa Putri has undulating landscape, with a variety of vegetation, stalactites and stalagmites. (2) Location Goa Putri tour object  situated near the Jalur Lintas Sumatra between baturaja and Muara Enim, (3) goa putri’s tour object has type A according Schmidth climate-Ferguson is very wet, (4) less favorable affordability levels as yet no transport straight to Goa Putri tour object that most tourists visiting by private vehicle, (5) Availability of facilities supported attractions Goa Putri existence cottage, toilets, bins, communication networks, cafeteria / kiosk, parking, safety fence. Key words: The social aid, Farmer, Poverty